Comparison of bleeding risk and hypofibrinogenemia-associated risk factors between tigecycline with cefoperazone/sulbactam therapy and other tigecycline-based combination therapies - Lei Zhang; Xinfeng Cai; Fangchen Peng; Shuangshuang Tian; Xinjing Wu; Yun Li; Jinlin Guo (Frontiers in Pharmacology, 2023)
Background: Tigecycline and cefoperazone/sulbactam can cause coagulation disorders; tigecycline may also lead to hypofibrinogenemia, raising safety concerns. This study aimed to investigate whether tigecycline plus cefoperazone/sulbactam increases the risk of bleeding compared with other tigecycline-based combination therapies and identify risk factors for tigecycline-associated hypofibrinogenemia.Methods: In this multi-method, multicenter, retrospective study, coagulation and other baseline variables were compared using a cohort study, and risk factors for hypofibrinogenemia using a case-control study.Results: The 451 enrolled participants were divided into three group: tigecycline plus cefoperazone/sulbactam (Group A, 193 patients), tigecycline plus carbapenems (Group B, 200 patients) and tigecycline plus β-lactams without N-methylthio-tetrazole (NMTT) side chains (Group C, 58 patients). Activated partial thromboplastin time and prothrombin time were prolonged, and fibrinogen declined for all patients after tigecycline-based medication (all p < 0.05). Prothrombin time in Group B was significantly longer than in other groups (p < 0.05), but there were no significant differences in bleeding events between the three groups (p = 0.845). Age greater than 80 years (OR: 2.85, 95% CI: 1.07–7.60), treatment duration (OR: 1.29, 95% CI: 1.19–1.41), daily dose (OR: 2.6, 95% CI: 1.29–5.25), total bilirubin (OR: 1.01, 95% CI: 1.01–1.02) and basal fibrinogen (OR: 1.32, 95% CI: 1.14–1.63) were independent risk factors of hypofibrinogenemia. The optimal cut-off for treatment course was 6 days for high-dose and 11 days for low-dose.Conclusion: Tigecycline plus cefoperazone/sulbactam did not increase the risk of bleeding compared with tigecycline plus carbapenem, or tigecycline plus β-lactam antibiotics without NMTT-side-chains. Coagulation function should be closely monitored in patients receiving tigecycline treatment.